Barrios to burbs : the making of the Mexican-American middle class - Agius Vallejo, Jody (Stanford University Press, 2012)
This study offers a new understanding of the Mexican-American experience. It explores the challenges that accompany rapid social mobility and examines a new indicator of incorporation, a familial obligation to 'give back' in social and financial support. The book investigates the salience of middle-class Mexican Americans' ethnic identification, and details how relationships with poorer co-ethnics and affluent whites evolve as immigrants and their descendants move into traditionally white middle-class occupations.